Characterization and phylogenetic analysis of the complete chloroplast genome of Ophiorrhiza pumila (Rubiaceae). Issue 7 (3rd July 2021) - Huang, Qikai; Kai, Guoyin
Abstract: Ophiorrhiza pumila (Rubiaceae) is an herbaceous plant that grows streamside in forest gullies or wetlands in the shade. Complete chloroplast genome of O. pumila was obtained and analyzed its phylogeny relationship within Rubiaceae plants. The results showed that the genome had a typical quadripartite structure of 154, 385 bp, and contained a total of 112 unique genes, including 79 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. Phylogenetic analysis suggested that O. pumila is sister to a highly supported clade composed of 10 species including Morinda officinalis, Gynochthodes cochinchinensis, Saprosma merrillii, Hedyotis ovata, Foonchewia guangdongensis, Dunnia sinensis, Paederia scandens, Leptodermis scabrida, Rubia cordifolia, and Galium mollugo . The complete chloroplast genome provides valuable information for the phylogenetic analysis of O. pumila.